LISTEN-READ-DISCUSS (LRD) IN TEACHING SECOND LANGUAGE READING - Yusanti, Elfa (LET: Linguistics, Literature and English Teaching Journal, 2018)
Reading is one of language skills that should be mastered by the students. In reading the text, readers can find the knowledge and get information from printed text. The students? reading comprehension of SMA Perintis 1 Bandar Lampung is still low especially in reading narrative text. The objective of this research is to know whether there is a significant influence of using LRD strategy towards students? reading comprehension on narrative text at the first semester of the eleventh grade of SMA Perintis 1 Bandar Lampung in 2017/2018 academic year. The research methodology was quasi experimental design. In this research, the population was the eleventh grade of SMA Perintis 1 Bandar Lampung. The sample of this research was two classes consisting of 25 students for experimental class and 25 students for control class. In the experimental class, the researcher used listen-read-discuss and in the control class the teacher used questioning strategy. The treatments were held in 5 meetings in which 2 x 45 minutes for each class. In collecting the data, the researcher used instrument in the form of multiple choice questions which had been tried out before the pretest. The instrument was given in pre-test and post-test. Before giving the treatment, the researcher gave pre-test for both classes. Then, after conducting the treatments, the instrument was given in post-test. After giving pre-test and post-test, the researcher analyzed the data using SPSS to compute independent sample t-test. Therefore, there is a significant influence of using listen-read-discuss towards students? reading comprehension of narrative text at the first semester of the eleventh grade of SMA Perintis 1 Bandar Lampung